The Housing ‘Problem’ Representations in Polish Housing Policy Discourse from 2016 to 2023 - Zubrzycka-Czarnecka, Aleksandra (Studia z Polityki Publicznej, 2024)
This paper utilises a Foucauldian-inspired policy discourse analysis, specifically employing Carol Bacchi’s ‘What’s the Problem Represented to Be’ approach, to explore the discursive construction of the housing ‘problem’. The focus of the research done for this paper was on housing policy discourse in Poland between 2016 and 2023. The study identifies two predominant representations of the housing ‘problem’: (1) the perception of an overly decommodified public sector and an inadequately decommodified private sector in housing; and (2) the insufficient support provided for middle-income families’ home-ownership. The reconstructed housing ‘problem’ representations relate to two political rationalities (discourse of sustainable development and housing rights, and neoliberal housing policy discourse) that shape the current housing policy in Poland. They have important implications for the housing domain (analysed as discursive effects, subjectification, and lived effects).